The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3389/fpsyt.2022.1063116
|View full text |Cite
|
Sign up to set email alerts
|

Neurobiological outcomes of cognitive behavioral therapy for obsessive-compulsive disorder: A systematic review

Abstract: IntroductionObsessive-compulsive disorder (OCD) is characterized by recurrent distressing thoughts and repetitive behaviors, or mental rituals performed to reduce anxiety. Recent neurobiological techniques have been particularly convincing in suggesting that cortico-striatal-thalamic-cortico (CSTC) circuits, including orbitofrontal cortex (OFC) and striatum regions (caudate nucleus and putamen), are responsible for mediation of OCD symptoms. However, it is still unclear how these regions are affected by OCD tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 94 publications
1
3
0
Order By: Relevance
“…However, the higher ACC activation was not observed in our results, and we speculate that this may be related to the fact that some OCD patients are taking medication. As previously reported, treatment may reduce ACC spontaneous activity ( 80 , 81 ).…”
Section: Discussionsupporting
confidence: 74%
“…However, the higher ACC activation was not observed in our results, and we speculate that this may be related to the fact that some OCD patients are taking medication. As previously reported, treatment may reduce ACC spontaneous activity ( 80 , 81 ).…”
Section: Discussionsupporting
confidence: 74%
“…Quarantine separates individuals potentially exposed to infections from the general population and can have psychological, emotional, and social consequences for some individuals (Hawryluck et al, 2004). Quarantine is an unpleasant experience that can separate a person from his or her friends and family (Poli et al, 2020). The quarantine period can lead to psychological consequences such as anxiety, aggression, and posttraumatic stress symptoms during the epidemic of infectious diseases.…”
mentioning
confidence: 99%
“…The presence of traumatic symptoms was met by a total of 36%, and shame and fear activations predicted the scores of traumatic scales, suggesting the importance of shame in the maintenance of traumatic symptoms related to COVID-19 experiences ( 29 ). Interestingly, in the National Comorbidity Survey Replication, those with a current diagnosis of PTSD were 3.62 times more likely to have obsessive-compulsive disorder (OCD) ( 30 33 ), and estimates of comorbidity (from 19% to 31%) vary based on the principal diagnosis considered and on whether considering current or lifetime (current and past) diagnoses ( 34 ). In addition, it has been reported that between 30% and 82% of those diagnosed with OCD have a trauma history ( 35 ).…”
Section: Introductionmentioning
confidence: 99%